2014
DOI: 10.4315/0362-028x.jfp-14-213
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Various Sanitizers against Salmonella during Simulated Commercial Packing of Tomatoes

Abstract: Chemical sanitizers are usually added to dump tank water to minimize cross-contamination during tomato packing. However, the efficacy of sanitizers continues to be questioned. This study assessed the ability of six commonly used sanitizers (40 ppm of peroxyacetic acid, 40 ppm of mixed peracid, 40 ppm of available chlorine alone or acidified to pH 6.0 with citric acid or T-128, and electrolyzed water containing 40 ppm of available chlorine at pH 6.7) to reduce Salmonella on tomatoes, in wash water, and on equip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 57 publications
1
5
0
1
Order By: Relevance
“…The WWW control showed reductions of 0.5-1.2 log CFU/fruit across all tested pathogens on cucumbers and tomatoes in this study. These results are similar to those of Wang and Ryser (2014), who 8 | A comparison of the reduction of Salmonella and surrogate E. faecium on tomatoes (log CFU/tomato) by triple-wash procedure WAW or WWA in water, SH (100 ppm, pH 8.2), ASH (SH, 100 ppm, pH 6.8 adjusted by citric acid), LCA (Veggiexide ® , 2.5%), and a PAA and hydrogen peroxide mix (SD, 0.0064, 0.25, and 0.50%). reported a 1.0 log CFU/g reduction of Salmonella from plain water wash for 15 s in a pilot-scale processing line.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The WWW control showed reductions of 0.5-1.2 log CFU/fruit across all tested pathogens on cucumbers and tomatoes in this study. These results are similar to those of Wang and Ryser (2014), who 8 | A comparison of the reduction of Salmonella and surrogate E. faecium on tomatoes (log CFU/tomato) by triple-wash procedure WAW or WWA in water, SH (100 ppm, pH 8.2), ASH (SH, 100 ppm, pH 6.8 adjusted by citric acid), LCA (Veggiexide ® , 2.5%), and a PAA and hydrogen peroxide mix (SD, 0.0064, 0.25, and 0.50%). reported a 1.0 log CFU/g reduction of Salmonella from plain water wash for 15 s in a pilot-scale processing line.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study suggest that the antimicrobial efficacy of chlorinated water in the concentration of 100 ppm was significant against Salmonella, and the reductions were improved when the pH of SH was adjusted to 6.8 in most cases, except for E. faecium on tomatoes. A previous study by Wang and Ryser (2014) also reported that chlorine plus citric acid (pH 6.0) yielded a greater reduction (3.1 log CFU/g) of Salmonella on tomatoes than chlorine at alkaline status (2.1 log CFU/g). This is because hypochlorous acid, the most effective antimicrobial component, predominates in chlorine water at near-neutral pH, whereas the hypochlorite would be in the ionic form rather than the antimicrobial protonated state in an alkaline-pH solution (White, 2010).…”
Section: Treatmentmentioning
confidence: 76%
“…Particularly, removal was the most influential model parameter for APC but was less influential for TC levels. Removal during washing via dump tanks or spray and brush systems has been studied for several produce commodities, and the importance of chlorine efficacy is well reported (29)(30)(31); however, it is also well established that removal of microorganisms from produce by chlorinated washing is unpredictable and prone to the cross-contamination of other products (32,33). Furthermore, growth rates at the packinghouse, distribution center, and retail storage were highly influential parameters, most likely due to long holding times and variable conditions suitable for survival and growth.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several sanitizers have been evaluated to inactivate foodborne pathogens on tomatoes, including electrolysed water (Wang and Ryser ), alkaline water (Islam et al . ), ozone (Mukhopadhyay et al .…”
Section: Introductionmentioning
confidence: 99%